ASSESSMENT OF MUSCULOSKELETAL CHANGES IN MENOPAUSE– A CROSS SECTIONAL STUDY - Doley Lakhiprova; Sarma Tikendrajit; Baishya Pranabjyoti (International Journal of Ayurveda and Pharma Research, 2020)
Menopause is associated with a natural decline in estrogen, progesterone and testosterone. These leads to certain health concern signs and symptoms like vasomotor symptoms, urogenital atrophy, cardiovascular diseases, psychological changes, decrease bone mass density leading to osteoporosis and fracture, diminished of muscle mass and strength. In Ayurveda, Rajanivritti is the word found in relation with menopause. In female, ageing influences Rajanivritti where Dhatuksyaya has observed. There is limitation of presence of sign and symptoms of Rajanivritti, except the age which is mentioned as 50 years. Increased of Vata dosa, imbalance in Pitta and Kapha with subsequence Anulumakkshyay are observed in ageing, leading to abnormalities in all Dhatus specially Mamsa and Asthidhatu. In this work muscle strength, joint movement, bone mass density (BMD) has observed in 60 menopause women, where significant alteration noted in muscle strength of upper extremities and bone mass density (BMD) shows osteopenia.